Self-rehabilitation in stressful situations (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article is devoted to the problem of psychological selfrehabilitation of a person in stressful situations and during a life crisis. Theessence of the concept of stress was investigated. There has been given stagesof development of stressful state and possible causes of its occurrence. Also,has been substantiated reasons for the current trend towards an increase inthe number of people with psychological problems. The scientific literaturewas reviewed regarding the psychology of extreme situations, psychologicalself-rehabilitation. The methods and techniques proposed by psychologistsfor dealing with stress and significance of difficulties in a person’s life wasanalyzed. And also was presented the results of a study regarding thestudents’ tendency to develop stress.
Keywords: stress; life crisis; extreme situations; psychological problems; self-rehabilitation